Potential Roles of Oral Microbiota in the Pathogenesis of Immunoglobin A Nephropathy - He, Jia-Wei; Zhou, Xu-Jie; Hou, Ping; Wang, Yan-Na; Gan, Ting; Li, Yang; Liu, Yang; Liu, Li-Jun; Shi, Su-Fang; Zhu, Li; Lv, Ji-Cheng; Zhang, Hong (Frontiers in Cellular and Infection Microbiology, 2021)
Disturbance in microbiota affects the mucosal immune response, and it is gradually recognized to be associated with the Immunoglobin A nephropathy (IgAN). This study aims to explore the potential roles of oral microbiota in disease pathogenesis. Saliva samples were collected from 31 patients with IgAN and 30 controls for 16S rRNA gene sequencing. The evenness, diversity, and composition of oral microbiota were analyzed. Moreover, sub-phenotype association analysis was conducted. Phylogenetic Investigation of Communities by Reconstruction of Unobserved States (PICRUSt) based on the Kyoto Encyclopedia of Genes and Genomes (KEGG) database was used to investigate microbiota functions. Compared to healthy controls, microbial diversity tended to decrease in IgAN, and the microbial profiles were remarkably distinguished. The relative abundance of Capnocytophaga and SR1_genera_incertae_sedis were enriched, whereas 17 genera, such as Rothia, were significantly reduced in IgAN. Variable importance in projection scores showed that 12 genera, including Capnocytophaga, Rothia, and Haemophilus, could discriminate between the two groups. In the sub-phenotype correlation analysis, the relative abundance of Capnocytophaga and Haemophilus was positively associated with levels of proteinuria and serum IgA, respectively. Further metabolic pathway analysis showed 7 predictive functional profiles, including glycosphingolipid biosynthesis, oxidative phosphorylation, and N-glycan biosynthesis were enriched in IgAN. In conclusion, disturbance in oral microbiota was observed to be associated with IgAN and its sub-phenotypes, which may shed novel insights into disease pathogenesis from a microbiome perspective.